Influence of the pulse duration of an ionizing electron beam on the efficiency of removal of sulfur oxides from smokestack gases; Technical Physics Letters; Vol. 20, № 4 - Kuznetsov D. L. (1994, 1994)
В фонде НТБ ТПУ отсутствует